Assessment of learning style preferences of pharmacy students: findings from public university of Malaysia - Elkalmi, Ramadan Mohamed Mahmod; Mohammed Ahmed, Abdul Kareem; Ahmad, Akram; Khan, Muhammad Umair; Ab Rahman, Norny Syafinaz; Alkoudmani, Ramez Mohmed (Association of Pharmaceutical Teachers of India (APTI), 2015)
Background: Student’s learning style preference is an important consideration for effective and high quality teaching and learning process. Different teaching approaches may not suit students’ preferences, hence, producing a gap between learning and delivery instructions. The aim of this study was to assess the learning style preferences among the first year pharmacy students of public sector university of Malaysia. Methods: A prospective cross sectional study was conducted during non-lecture hour using validated VAK (visual, aural, and kinaesthetic) questionnaire. After a brief description about the study, the questionnaire was distributed to investigate student’s learning mode preferences. Results: A total of 118 responses were received, giving a response rate of 100%. Unimodal learning style was preferred by majority of the students (94.07%). Specifically, visual approach of learning was commonly reported by the participants (53.4%), followed by kinaesthetic mode (22.88%) and auditory mode (17.8%) respectively. Bimodal and tri-modal learning approach was preferred by 5.08% and 0.85% patients respectively. Gender, residency, number of siblings and parent’s income did not influence learning preferences of pharmacy students indicating no significance association between the factors and learning styles of the students. Conclusion: The study concluded that teaching styles should be adapted to accommodate the preferences of learning styles among pharmacy students to improve the quality of the teaching and learning experiences of pharmacy students.